RELEVANCE OF ISLAMIC ECONOMIC THOUGHT ACCORDING TO MUHAMMAD BAQIR AL-SADR IN THE CONTEXT OF SOCIAL JUSTICE ECONOMY - Sriutami, Wahyu; Rozalinda, Rozalinda; Zulvianti, Nora (Jaksya: Jurnal Akuntansi Syariah, 2025)
Background of the problem in this study is an increase in Earning Per Share (EPS) and Return On Equity (ROE) which is not followed by an increase in stock prices, this is not in accordance with theory that says that when Earning Per Share and Return On If equity rises, the stock price will also rise. Purpose of this study is to find out the effect of Earning Per Share (EPS), Return On Equity (ROE) against the stock price, and to find out whether the size of the The company moderated the influence of EPS and ROE on the stock price. This type of research is quantitative research, Index from the www.idx.co.id site. and the annual report of the company concerned. This study uses purposive sampling with the criteria of companies that have consistently entered JII in the last 10 years, so that the sample used is 7 samples. The data analysis techniques used are Descriptive Statistics, Classical Assumption test, panel data model selection test, hypothesis test and MRA test. This study was analyzed using a statistical tool, namely Eviews 10. Based on the results of this study, the partial test and MRA test can be concluded that the Earning Per Share (EPS) variable affects the stock price of companies listed in the Jakarta Islamic Index. that the Return On Equity (ROE) variable has an effect on the share price of companies listed in the Jakarta Islamic Index, the Return On Equity (ROE) variable has an effect on the share price of companies listed in the Jakarta Islamic Index, the size of the company is able to moderate (strengthen) the effect of EPS on the share price of companies listed in the Jakarta Islamic Index, the size of the company is not able to moderate (strengthen) the effect of ROE on the share price of companies listed in Jakarta Islamic Index.